An Arabidopsis WD40 repeat-containing protein XIW1 promotes salt inhibition of seed germination. (1st February 2020) - Cai, Jiajia; Huang, Haijian; Xu, Xuezhong; Zhu, Guohui
ABSTRACT: WD40 repeat-containing protein (WD40 protein) acts as versatile scaffolds for protein interactions and participates in a variety of biological processes, such as plant stress and hormone responses. In a recent study, we show that XPO1-Interacting WD40 protein 1 (XIW1) is nuclear accumulated by abscisic acid (ABA), which interacts with ABA insensitive 5 (ABI5) in the nucleus and maintains its stability, thereby affecting seed germination and seedling growth. Here, we show that XIW1 promotes salt inhibition of seed germination (SSG). Mutation of XIW1 reduced the induction of ABI5 and ABA-responsive genes under salt treatment, causing mutant plants with high seed germination and suppression of SSG. In addition, we found that salt treatment facilities XIW1 accumulation in the nucleus. These findings reveal the important role of XIW1 in the regulation of SSG and provide a possible mechanism of XIW1 affecting SSG.